Dilemmas of Discourse: Legitimising Britain's War on Terror. (May 2013) - Kettell, Steven
The sphere of foreign policy provides a hitherto unexplored field for studying the applicability of interpretivist concepts and concerns. Here, a particularly useful topic of analysis is that of discursive strategies; namely, the way in which government figures seek to legitimise and justify their decisions and behaviour. Operating at the intersection between beliefs, traditions and dilemmas, the examination of foreign policy discourse offers key insights into a variety of important issues, including political communication and media management. This article considers these themes by examining the changing form of New Labour's discursive strategy on Britain's role in the war on terror during the period of Tony Blair's premiership from 2001 to mid-2007. Charting the various shifts to have taken place in this discursive landscape, the article analyses the way in which these changes were driven by dilemmas resulting from tensions between practical developments and the discursive claims made about them. This shows how various rationalities within the sphere of British politics were operationalised and sustained, and how numerous 'dilemmas of discourse' were addressed.